(untitled) (Homiletic, 2019)
Addressing the preacher’s need to identify their social locations as a preacher, this article explores three critical approaches for homiletics in the postcolonial context of migration: interdisciplinary, intercultural, and interreligious. The interdisciplinary approach to homiletics was sought in the New Homiletic movement but has yet to be fully pursued. Continued dialogue with other disciplines is urgent in a context where complicated postcolonial realities must be addressed. The intercultural issues of preaching are equally important in this context. This paper, therefore, sketches the changing ecclesial landscape where a monolingual homogeneous white congregation and preacher are no longer a norm. How can preaching reflect multivocality and prevent linguistic minority members from being tokenized? The power imbalance embedded in the language of the preacher needs consideration. The interreligious approach has only recently appeared on the horizon of homiletical thought, challenging the Christian-supremacist positions and interpretative practices. Overcoming Christian-centrism, the article argues, can happen once the fear of the other, the fear of difference, and the fear of mixing are acknowledged in the preaching event. Interreligious reality is unfolding and inevitable as a marker of our postcolonial migration context. It potentially ushers in an exciting opportunity for the study of Christian preaching, if we are willing to embrace it.